Batik Rifa'iyah Sebagai Dokumen - Kamil, Rusdan; Fitriani, Dian Novita; Khatimah, Khusnul (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2021)
Batik is a work of visual art in the form of traditional clothing, and intangible cultural heritage has become an inseparable part of the daily life of the Indonesian people. One of the motives is the famous Rifa'iyah batik with a pattern inspired by the teachings of Sheikh Ahmad Rifa'i which shows evidence of the beliefs, deeds, and identity of Sheikh Ahmad Rifa'i's followers. In this study, the author aims to discuss Batik Rifa'iyah as a document using conceptual analysis based on document theory such as the concept of meaningful, indexicality, and documents as a broader system to explore the meaning contained in Batik Rifa'iyah styles. This study provides an alternative understanding of batik cloth, especially batik rifa'iyah which is not limited to cloth and visual arts but also provides an in-depth analysis of how to treat colors, shapes, and patterns as documents that refer to the daily life of the Rifa'iyah people. This research also extends the use of document theory in analyzing various information objects in the neodocumentation movement tradition. The results show that batik rifa'iyah has enriched our view of documents, which are symbolic representations, not only expressed through words that have long been known, but lines, colors, and shapes are indeed essential things of a document.